2013
DOI: 10.1038/nature12186
|View full text |Cite
|
Sign up to set email alerts
|

Hofstadter’s butterfly and the fractal quantum Hall effect in moiré superlattices

Abstract: Electrons moving through a spatially periodic lattice potential develop a quantized energy spectrum consisting of discrete Bloch bands. In two dimensions, electrons moving through a magnetic field also develop a quantized energy spectrum, consisting of highly degenerate Landau energy levels. When subject to both a magnetic field and a periodic electrostatic potential, two-dimensional systems of electrons exhibit a self-similar recursive energy spectrum. Known as Hofstadter's butterfly, this complex spectrum re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

62
1,489
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,633 publications
(1,559 citation statements)
references
References 30 publications
62
1,489
5
3
Order By: Relevance
“…Upon intercalation of Li, the optical properties of few-layer graphene crystals (with thicknesses down to 1 nm) change significantly [4], Ca-intercalated few-layer-graphene is superconducting [5], and FeCl3 intercalated bilayer graphene showed a hint of ferromagnetism [6]. In addition, there have been theoretical predictions that heavy doping and proximity induced spin-orbit coupling from certain intercalants may induce exotic electronic properties in the graphene channel [7].Recently, it was demonstrated that one can stack different van der Waals (vdW) atomic layers to form vdW heterostructures, creating a new generation of few-atomic-layer functional heterostructures with emergent properties [8,9]. In particular, graphene encapsulated by h-BN, a layered insulator, forms a vdW heterostructure where the 2-dimensional (2D) graphene channel is well isolated from the environment [8].…”
mentioning
confidence: 99%
“…Upon intercalation of Li, the optical properties of few-layer graphene crystals (with thicknesses down to 1 nm) change significantly [4], Ca-intercalated few-layer-graphene is superconducting [5], and FeCl3 intercalated bilayer graphene showed a hint of ferromagnetism [6]. In addition, there have been theoretical predictions that heavy doping and proximity induced spin-orbit coupling from certain intercalants may induce exotic electronic properties in the graphene channel [7].Recently, it was demonstrated that one can stack different van der Waals (vdW) atomic layers to form vdW heterostructures, creating a new generation of few-atomic-layer functional heterostructures with emergent properties [8,9]. In particular, graphene encapsulated by h-BN, a layered insulator, forms a vdW heterostructure where the 2-dimensional (2D) graphene channel is well isolated from the environment [8].…”
mentioning
confidence: 99%
“…The above result indicates that the new compound is composed of the triangular-lattice Rh In general, two triangular lattices coupled at a twist angle form a quasiperiodic structure that has no unit cell. [18][19][20][21] As evidenced by the in-plane x-ray and electron diffractions (Figures 2e and 3j), however, the new layered compound shows periodically modulated hexagonal patterns with the in-plane cell parameter of 8.05(±0.05) Å. The selected-area electron diffraction detects the single pattern from only one type of the two crystallographic domains, while their both patterns are observed in the entire-area in-plane XRD.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, in the research field of atomic layer materials such as graphene or transition metal dichalcogenides, the twist angle has been recognized as a new important parameter for tuning electrical and optical properties of stacked layers. [18][19][20][21] In the following, we present a new compound with a twisted stack of oxide layers stabilized by epitaxy technique. For this purpose, we adopt a simple Bi-Rh-O system, because Bi with a relatively large ionic radius is expected to form a large triangular-lattice layer mismatched to the RhO 2 layer.…”
Section: Introductionmentioning
confidence: 99%
“…The perturbation produced by the moiré superlattice results in the formation of mini- bands for Dirac electrons in graphene [13][14][15][16][17][18][19][20]. The latter can be found by numerical diagonalisation of the moiré superlattice Hamiltonian,…”
mentioning
confidence: 99%
“…1. For the unstrained heterostructure (left) the spectrum exhibits a secondary Dirac point [13][14][15][17][18][19] in the valence band. Strain, as low as w ∼ 1 − 3%…”
mentioning
confidence: 99%